On the diversity and distribution of a data deficient habitat in a poorly mapped region: The case of Sabellaria alveolata L. in Ireland. (July 2021) - Firth, Louise B.; Curd, Amelia; Hawkins, Stephen J.; Knights, Antony M.; Blaze, Julie A.; Burrows, Michael T.; Dubois, Stanislas F.; Edwards, Hugh; Foggo, Andy; Gribben, Paul E.; Grant, Lisa; Harris, Daniel; et al.
Abstract: Data that can be used to monitor biodiversity through time are essential for conservation and management. The reef-forming worm, Sabellaria alveolata (L. 1767) is currently classed as 'Data Deficient' due to an imbalance in the spread of data on its distribution. Little is known about the distribution of this species around Ireland. Using data archaeology, we collated past and present distribution records and discovered that S. alveolata has a discontinuous distribution with large gaps between populations. Many regions lack data and should be targeted for sampling . Biodiversity surveys revealed that S. alveolata supported diverse epibiotic algal communities. Retrograding (declining) reefs supported greater infaunal diversity than prograding (growing) reefs or sand, suggesting that S. alveolata is a dynamic ecosystem engineer that has a lasting legacy effect. Similar research should be carried out for other Data Deficient species, habitats and regions. Such data are invaluable resources for management and conservation. Graphical abstract: Image 1 Highlights: Improving the knowledge base of data deficient species will enable greater protection. We identified knowledge gaps for the distribution of a Data Deficient species in a poorly mapped region. S. alveolata reefs supported diverse epibiotic algal assemblages. Retrograding (declining) reefs supported greater infaunal diversity than prograding (growing) reefs. Such research should be done for other Data Deficient species and habitats.